Dataset: The Anthropocene reality of financial risk - Crona, Beatrice; Folke, Carl; Galaz, Victor (Stockholm University, 2021)
This dataset was generated during the study The Anthropocene reality of financial risk. It contains two separate datasets in the form of csv files, and Supplemental Experimental Procedures which contain details on the analysis conducted, as well as data on capital allocated to different investment instruments in 2019, collated from publically available sources. Some restrictions may apply to the use of the Refinitiv Eikon® (Thomson Reuters) data as this was obtained under paid license.
Keywords: Earth and Environmental Sciences; Social Sciences; ESG; deforestation risk; debt; Sustainable Finance; observation data/ratings, secondary textual/numerical data; Social Sciences; Samhällsvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap